Human effector/initiator gene sets that regulate myometrial contractility during term and preterm labor - Weiner, Carl P.; Mason, Clifford W.; Dong, Yafeng; Buhimschi, Irina A.; Swaan, Peter W.; Buhimschi, Catalin S. (American journal of obstetrics and gynecology, 2010)
Distinct processes govern transition from quiescence to activation during term (TL) and preterm labor (PTL). We sought gene sets that are responsible for TL and PTL, along with the effector genes that are necessary for labor independent of gestation and underlying trigger. Expression was analyzed in term and preterm with or without labor (n = 6 subjects/group). Gene sets were generated with logic operations. Thirty-four genes were expressed similarly in PTL/TL but were absent from nonlabor samples (effector set); 49 genes were specific to PTL (preterm initiator set), and 174 genes were specific to TL (term initiator set). The gene ontogeny processes that comprise term initiator and effector sets were diverse, although inflammation was represented in 4 of the top 10; inflammation dominated the preterm initiator set. TL and PTL differ dramatically in initiator profiles. Although inflammation is part of the term initiator and the effector sets, it is an overwhelming part of PTL that is associated with intraamniotic inflammation.